GONDWANA ALIVE CORRIDORS: EXTENDING GONDWANA RESEARCH TO INCORPORATE STEMMING THE SIXTH EXTINCTION - de Wit M.J.; Anderson J.M. (My University, 2003)
In this volume in honour of John Rogers we propose a new way of looking at Gondwana and we urge our colleagues everywhere to join us in this venture. The Gondwana Alive Corridors provide a way of celebrating the unique geological, biological and cultural heritage of the Gondwana continents, and they offer a focus for the holistic management of that heritage. Here we explore a set of 15 prototype corridors from around Gondwana which together weave a tapestry of our prodigiously diverse planet. This Earth-history tapestry traces geological time from the oldest crust to the youngest ice sheets and from the earliest known life to the current activities of our human family. The corridors, in proliferating number, offer a science-based strategy towards stemming the Sixth Extinction.
Keywords: Gondwana AZive Corridors; Sixth Extinction; biodiversity; consilience; Earth System Science